2012
DOI: 10.1007/s10895-012-1111-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Determination of Azithromycin in Pharmaceutical Formulations by Using the Synchronous Scanning Approach After its Acid Derivatization

Abstract: In this present work, a fluorescence method for azithromycin (9-deoxo-9a-aza-9a-methyl-9a-homoerythromycin) determination in pharmaceutical formulations is proposed. The method is based on the synchronous fluorescence (Δλ = 30 nm, 482 nm) produced when azithromycin is derivatized in strong acidic medium (9.0 mol L(-1) HCl). The influence of the derivatization conditions (acid concentration, reaction time and temperature) was studied. Also, the possible reaction mechanism was discussed. In the optimized conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, excessive use can lead to resistance, negatively impacting infection management. Furthermore, AZM has been detected in aquatic environments at high concentrations, requiring the development of more accurate and efficient analytical methods, [5] including high‐performance liquid chromatography (HPLC), [6] gas chromatography with mass spectroscopy (GC‐MS), [7] colorimetry, [8] spectrofluorometer, [9] and UV‐Vis spectroscopy [10] . These methods have drawbacks such as high cost, lengthy analysis time, and complex sample preparation process [11] .…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive use can lead to resistance, negatively impacting infection management. Furthermore, AZM has been detected in aquatic environments at high concentrations, requiring the development of more accurate and efficient analytical methods, [5] including high‐performance liquid chromatography (HPLC), [6] gas chromatography with mass spectroscopy (GC‐MS), [7] colorimetry, [8] spectrofluorometer, [9] and UV‐Vis spectroscopy [10] . These methods have drawbacks such as high cost, lengthy analysis time, and complex sample preparation process [11] .…”
Section: Introductionmentioning
confidence: 99%
“…As for AZT, it has been determined by high performance liquid chromatography (HPLC) [3][4][5][6], liquid chromatography-mass detection (LC-MS/MS) [7,8], ultra-performance liquid chromatography (UPLC) [9], micellar liquid chromatography (MLC) [10], spectroflourimetry [11] and UVVisible spectrophotometry [12][13][14][15][16][17] while ROX has been estimated by HPLC [18,19], LC-MS/MS [20], spectroflourimetry [21,22] and UV-Visible spectrophotometry [23].…”
Section: Introductionmentioning
confidence: 99%
“…1). Literature reveals few spectrophotometric methods [18][19][20][21][22][23] and two fluorimetric assays [24,25] for determination of AZN in bulk and formulations. A detailed review for RSGL estimation [26] is reported, without direct fluorimetric technique.…”
mentioning
confidence: 99%